2003
DOI: 10.1097/00006123-200301000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Diverticula in Obstructive Hydrocephalus Secondary to Tumor Growth

Abstract: Ventricular diverticula should be distinguished from other cystic lesions in the quadrigeminal region. Detection of an ostium of a diverticulum or communication between the cyst and the ventricular system is important for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In the presence of local pathological factors, a direct surgical approach to remove an obstructive lesion is indicated for the treatment of hydrocephalus and ventricular diverticula [16]. If such an approach is not effective, however, ventricular shunting is probably the least dangerous and most effective method of treatment for uncomplicated diverticula, although endoscopic ventriculostomy may be indicated for selected patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of local pathological factors, a direct surgical approach to remove an obstructive lesion is indicated for the treatment of hydrocephalus and ventricular diverticula [16]. If such an approach is not effective, however, ventricular shunting is probably the least dangerous and most effective method of treatment for uncomplicated diverticula, although endoscopic ventriculostomy may be indicated for selected patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…In another recent report, Abe et al [1] demonstrated clearly by cine MRI that the lateral ventricular diverticulum flows into the supracerebellar cistern near the antrum of the lateral ventricle. Based on these findings, they confirmed the herniation route of the lateral ventricular diverticulum through the medial antrum into the supracerebellar cistern.…”
Section: Discussionmentioning
confidence: 99%
“…A ventricular diverticulum has rarely been found in children or adults with long-standing severe obstructive hydrocephalus due to obstruction of the foramen of Monro, foramen of Magendi, and intra- or juxtaventricular tumors [1,2,3,4,5,6]. There have been few cases of infants reported in the past literature [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraventricular diverticulum are extensions or focal outpouching of the ventricle lined by a prolapsed ependymal layer. [ 2 3 ] It occurs in the setting of longstanding hydrocephalus and resolves following treatment for hydrocephalus. The common causes include post neuroendoscopy, shunt placements, hemorrhage, and clinically silent focal ischemia.…”
mentioning
confidence: 99%